World literature, transnational cinema, and global media towards a transartistic commons - Stam, Robert 1941- (Routledge, Taylor & Francis Group, 2019)
"With extraordinary transnational and transdisciplinary range, World Literature, Transnational Cinema, and Global Media comprehensively explores the genealogies, vocabularies, and concepts orienting the fields within literature, cinema and media studies. Orchestrating a layered conversation between arts, disciplines, and media, Stam argues for their "mutual embeddedness" and their shared "in-between" territories. Rather than merely add to the existing scholarship, the book builds a relational framework through the connectivities within literature, cinema and media that opens up analysis to new categories and concepts, whilst crossing spatial, temporal, theoretical, disciplinary, and mediatic borders. The book also questions an array of hierarchies: literature over cinema; source novel over adaptation; feature film over documentary; erudite over vernacular culture; western modernisms over "peripheral" modernisms; classical over popular music; written poetry over sung poetry, and so forth. The book is structured around the concept of the "Commons," forming a strong thread which links various struggles against "enclosures" of all kinds, with emphasis on natural, indigenous, cultural, creative, digital, and the transdisciplinary commons. World Literature, Transnational Cinema, and Global Media is ideal to further the theoretical discussion for those undergraduate and graduate departments in cinema studies, media studies, arts and art history, communications, journalism, and new digital media programs at all levels"-- Provided by publisher.